2000
DOI: 10.1055/s-2000-6244
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Dealkylation of 2-Alkoxybenzoic Acid and Its Amide Derivatives with Aliphatic Amines

Abstract: The methoxy group of o-anisic acid was cleaved with aliphatic amines in aprotic dipolar solvents. This cleavage reaction was especially smooth when piperazine in dimethylacetamide was used. This method was applicable to a variety of dealkylations of o-alkoxybenzoic acid and ist amide derivatives with high regioselectivity.For the demethylation of o-anisic acid (o-methoxybenzoic acid) and amide derivatives, dealkylation methods used for the O-alkyl protective group of phenols 1 can generally be applied. A numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The method was feasible only for the synthesis of compound 38 and 39 . In case of the ortho-substituted compound 37 , the final demethylation was successfully carried out under basic conditions using piperazine in dimethyl acetamide at 150 °C …”
Section: Resultsmentioning
confidence: 99%
“…The method was feasible only for the synthesis of compound 38 and 39 . In case of the ortho-substituted compound 37 , the final demethylation was successfully carried out under basic conditions using piperazine in dimethyl acetamide at 150 °C …”
Section: Resultsmentioning
confidence: 99%
“…Buckle et al, 17 reported dealkylation of (2methoxyphenyl) ethynes using lithium iodide in refluxing 2, 4, 6-trimethylpyridine. 18 Nishioka et al, 19 found that ortho anisic acid can be demethylated with aliphatic amines in high boiling aprotic solvents like DMSO, DMF, and dimethyl acetamide at temperatures around 150 • C. It occurred to us that it may be possible to synthesize 1 under mild basic conditions from nitrocatechol precursors like 3.…”
Section: Demethylation By Nucleophilic Attackmentioning
confidence: 99%
“…Nishioka et al disclosed the ortho-selective demethylation of methoxy substituted benzoic acids and primary and secondary benzamides in the presence of piperazine (3 eq) in N,Ndimethylacetamide at 150 °C. 24 Later, the reaction was carried out in 1-methylpyrrolidin-2-one at 140 °C to prepare variously substituted ortho-hydroxybenzamides. 25 A regioselective aryl methyl ether cleavage was observed in the presence of phenylethylamine at 200 °C.…”
Section: Introductionmentioning
confidence: 99%